Comparison of the Broth Microdilution (BMD) Method of the European Committee on Antimicrobial Susceptibility Testing with the 24-Hour CLSI BMD Method for Testing Susceptibility of Candida Species to Fluconazole, Posaconazole, and Voriconazole by Use of Epidemiological Cutoff Values - Pfaller, M. A. (American Society for Microbiology, 2011)
The antifungal broth microdilution (BMD) method of the European Committee on Antimicrobial Susceptibility Testing (EUCAST) was compared with CLSI BMD method M27-A3 for fluconazole, posaconazole, and voriconazole susceptibility testing of 1,056 isolates of Candida. The isolates were obtained in 2009 from more than 60 centers worldwide and included 560 isolates of C. albicans, 175 of C. glabrata, 162 of C. parapsilosis, 124 of C. tropicalis, and 35 of C. krusei. The overall essential agreement (EA) between EUCAST and CLSI results ranged from 96.9% (voriconazole) to 98.6% (fluconazole). The categorical agreement (CA) between methods and species of Candida was assessed using previously determined epidemiological cutoff values (ECVs). The ECVs (expressed as μg/ml) for fluconazole, posaconazole, and voriconazole, respectively, were as follows: 0.12, 0.06, and 0.03 for C. albicans; 32, 2, and 0.5 for C. glabrata; 2, 0.25, and 0.12 for C. parapsilosis; 2, 0.12, and 0.06 for C. tropicalis; 64, 0.5, and 0.5 for C. krusei. Excellent CA was observed for all comparisons between the EUCAST and CLSI results for fluconazole, posaconazole, and voriconazole, respectively, for each species: 98.9%, 93.6%, and 98.6% for C. albicans; 96.0%, 98.9%, and 93.7% for C. glabrata; 90.8%, 98.1%, and 98.1% for C. parapsilosis; 99.2%, 99.2%, and 96.8% for C. tropicalis; 97.1%, 97.1%, and 97.1% for C. krusei. We demonstrate high levels of EA and CA between the CLSI and EUCAST BMD methods for testing of triazoles against Candida when the MICs were determined after 24 h and ECVs were used to differentiate wild-type (WT) from non-WT strains. These results provide additional data in favor of the harmonization of these two methods.